Shadow pitching deviates ball release position: kinematic analysis in high school baseball pitchers - Shigeaki Miyazaki; Go Yamako; Koji Totoribe; Tomohisa Sekimoto; Yuko Kadowaki; Kurumi Tsuruta; Etsuo Chosa (BMC, 2021)
Abstract Background Although shadow pitching, commonly called "towel drill," is recommended to improve the throwing motion for the rehabilitation of pitching disorders before the initiation of a throwing program aimed at returning to throwing using a ball, the motion differs from that of normal throwing. Learning improper motion during ball release (BR) may increase shoulder joint forces. Abnormal throwing biomechanics leads to injures. However, there has been no study of shadow pitching focusing on the BR position. The purpose of the present study was to evaluate the BR position and kinematic differences between shadow pitching and normal throwing. In addition, the effect of setting a target guide for BR position on throwing motion was examined in shadow pitching. Methods The participants included in this study were 20 healthy male students who were overhand right-handed pitchers with no pain induced by a throwing motion. Participants performed normal throwing (task 1), shadow pitching using a hand towel (task 2), and shadow pitching by setting a target of the BR position (task 3). A motion capture system was used to evaluate kinematic differences in throwing motions, respectively. Examination items comprised joint angles and the differences in BR position. Results BR position of task 2 shifted significantly toward the anterior, leftward, and downward directions compared with task 1. The distance of BR position between tasks 1 and 2 was 24 ± 10%. However, task 3 had decreased BR deviation compared with task 2 (the distance between 3 and 1 was 14 ± 7%). Kinematic differences were observed among groups at BR. For shoulder joint, task 2 showed the highest value in abduction and horizontal adduction among groups. In spine flexion, left rotation and thorax flexion, task 2 was significantly higher than task 1. Task 3 showed small differences compared with task 1. Conclusions The BR position of shadow pitching deviated significantly in the anterior, leftward, and downward directions compared with normal throwing. Furthermore, we demonstrated that the setting of BR target reduces this deviation. Thus, the target of BR position should be set accurately during shadow pitching exercises in the process of rehabilitation.